Transmission of Arabic Islamic Culture Through Literature / نقل الثقافة العربية الإسلامية عبر الأدب والإعلام - Amar Al-Khateeb; Müller. H (IJAS: International Journal of Arabic Studies, 2025)
This study investigates the transmission of Arabic Islamic culture through literature and media, examining how cultural meanings, values, and historical narratives are preserved, reshaped, and disseminated across contemporary communication channels. Through a qualitative analytical approach, the research explores the dynamic interaction between classical literary heritage, modern digital media, and audience reception across diverse cultural contexts. The findings highlight significant shifts in cultural transmission patterns shaped by globalization, technological advancements, and the emergence of new media forms. Moreover, the study reveals existing gaps in how cultural authenticity is maintained, particularly when traditional texts are adapted into modern digital formats. This research contributes to a deeper understanding of how Arabic Islamic cultural identity is negotiated and reproduced in the present era, offering insights relevant for scholars of cultural studies, media studies, and Arabic literature. Ultimately, the study underscores the need for strengthened frameworks that ensure accurate, ethical, and contextually grounded representation of Arabic Islamic culture in both local and global platforms.